Strategi Kepala Madrasah dalam Meningkatkan Kemampuan Literasi Digital Guru pada Masa Pandemi Covid-19 - M. Yusuf; Ahmad Saifudin; Afi Nuruz Zahrok (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
The onslaught of the Covid-19 pandemic has attacked all sectors of people's lives, including the education sector. Therefore, education managers are required to always respond swiftly by always thinking creatively and innovatively both in terms of systems and learning mechanisms in order to survive in the midst of a pandemic, including improving the competence of educators, especially in the field of digital literacy. This study aims to answer the question of how the madrasa principal's strategy is to improve the digital literacy skills of teachers during the covid-19 pandemic, how it is implemented and how to evaluate the madrasa principal's strategy. To achieve these objectives, this study used a qualitative approach with a descriptive type. Data collection techniques were carried out through observation, interviews and documentation studies. Data analysis techniques are data reduction, data presentation, and verification. The research subjects were the Head of Madrasah, Deputy Head of Madrasah, and Teachers. The object of this research is at MAN 1 Nganjuk. This study proves that the formulation of the madrasa principal's strategy in improving the digital literacy skills of teachers during the covid-19 pandemic by providing assistance to madrasa e-learning applications and synergizing with fellow teachers, in its implementation, the madrasa head implements government regulations based on circulars by providing assistance and urges to pay close attention to the appropriateness of news or information properly and to provide flexibility for teachers to take part in workshops outside madrasa institutions. Meanwhile, strategy evaluation is carried out by intensifying supervision to determine the realization of behavior in the organization with the desired one through the monitoring menu and teacher performance assessment.